Justice and justification in Matthew and James: a challenge for lutheran hermeneutics today - Niebuhr, Karl-Wilhelm (Vox Scripturae - Revista Teológica Internacional, 2017)
The article discusses the importance of the biblical testimony on justice and justification for contemporary Lutheran hermeneutics. Based on the fact of Luther’s critical statements in his prefaces to the German translation of the Bible on the Epistle of James and from his estimation of the Gospel of Matthew, the essay explores the role and function of these two NT writings in recent ecumenical projects on the doctrine of justification. Thereafter, the meaning of justice in James and Matthew in contemporary exegetical research is described. In the conclusion, the relationship between Paul’s doctrine of justification and the testimony on justice in James and Matthew is delineated.